Pemanfaatan Tanah Lempung Sebagai Koagulan Dalam Penurunan Konsentrasi Zat Organik (KMnO4) Pada Air Gambut Dengan Proses Two-stage Coagulation - Aldita Meitri Dewi; Shinta Elystia; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Organic matter in peat water can react with chlorine during the chlorinationprocess that cause the formation of trihalomethans (THMs) which can cause acancer because it’s carcinogenic. Organic matter also hard to be removed bytraditional coagulation (one-stage) due to its hydrophobic and hydrophilicfractions that requiring another alternative treatment like two-stage coagulationby using clay as a coagulant. Research using a jar test by varying the mass ofcoagulant that is 1, 2, 3, 4, 5 and 6 gr. In two-stage process, coagulant also splitequally for first and second coagulation with variations 1/3:2/3, 1/2:1/2 and2/3:1/3. The result showed that the highest efficiency for two-stage coagulationcan achieved 94,45% at addition of 5 gr of coagulant with 2/3:1/3 varian ofcoagulant split and already met the standard. Then the characterization offunctional bunch of organic matter doing by FTIR spectra and the result showedthat the functional bunch of hydrophobic like C-O from esthers, ethers andphenols bunch and C-C from aromatic bond also hydrophilic bunch like O-Halcohol can not be detected after two-stage coagulation process.Keywords : Peat water, organic matter, clay and two-stage coagulation